Penerapan Restorative Justice Dalam Penyelesaian Perkara Tipiring (Tindak Pidana Ringan) - Januar Januar; Tengku Maulana Syah; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Settlement of cases using the litigation route in practice does not always go according to what is expected and aspired to by the Indonesian people. because the settlement of cases using the litigation route in the current criminal justice system actually creates new problems, for example the pattern of punishment that is still retaliatory in nature, causes a buildup of cases, does not pay attention to the rights of victims, is not in accordance with the principle of simple justice. But the process is long, complicated and expensive, the settlement is legal and rigid, does not restore the effects of crime, does not reflect justice for society and so on. Even though the law is actually made to provide justice and benefits for humans which is reflected in the values of Pancasila. Seeing these various phenomena, in recent developments a new concept has emerged, namely the concept of restorative justice. The concept or approach of restorative justice is considered to be able to overcome various problems in the criminal justice system as mentioned above. Settlement of ordinary crimes with mild motives can be reached by means of penal mediation called a restorative justice approach, which focuses on the direct participation of perpetrators, victims and the community by interpreting criminal acts. Restorative justice is also a new framework of thinking that can be used in response to a crime for law enforcement in Indonesia. This research will discuss the application of restorative justice in the settlement of minor crimes. This research is a normative legal research which is descriptive analytical. The approach used is a statutory approach, a conceptual approach and an approach to legal principles (Azhar, 2019). Keywords: restorative justice, application of the concept, misdemeanors